The Benefits Of Mental Health Promotion In School Environments On Improving Emotional Well-Being In Adolescents - Bergita Dumar; Nur Fitriah Jumatrin; Sri Yulian Hunowu; Ida Wahyuni; Dedi Krismiadi (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Adolescents are an age group that experiences puberty which is marked by physical and psychological changes. The demands of facing challenges during this period can affect the emotional well-being of adolescents. Improving emotional well-being in adolescents can involve the role of schools because in general adolescents will spend more time at school with their peers. Schools are considered to be the right place to promote mental health. This study aims to see the benefits of mental health promotion in the school environment on improving emotional well-being in adolescents. This study is a quasi-experimental study with a control group pre-posttest design. The sampling technique used Stratified Random Sampling with a total sample of 70 adolescents aged 15-18 years from one of the Senior High Schools (SMA) in East Kolaka Regency, Southeast Sulawesi. Assessments related to emotional well-being were assessed using the Strengths and Difficulties Questionnaire (SDQ). There was a significant difference between the pre-test and post-test after mental health promotion in the school environment on improving emotional well-being by showing a p-value <0.005. The results of the study indicate that mental health promotion in the school environment has a significant effect on improving emotional well-being in adolescents. Due to the great benefits of mental health promotion, it is highly recommended for schools to integrate mental health promotion into school activities to improve emotional well-being in adolescents.